Malay Proverbs (meaning-making through digital visual literacy) / Neesa Ameera Mohamed Salim and Mohd Nor Shahizan Ali - Mohamed Salim, Neesa Ameera; Ali, Mohd Nor Shahizan (Universiti Teknologi MARA, Kedah, 2018)
Proverbs are also known as traditional sayings or popular epigram which are generally simple, concrete and often metaphorical which expresses a traditionally held truth or advice based on the lifestyle of the community. In Malaysia, Malay proverbs are often used by the Malaysian community, which is an Asian ethnicity rich with culture and wisdom. The Malay proverbs are often communicated in natural language used to understand the world view and to express a specific point which consequently signifies the non-logical elements of the Malay mind. In today's digital age, it is essential to cultivate the Malay proverbs using digital visual platforms to preserve the informational and rhetorical elements which also reflects the Malay culture.